Moral resilience and intention to leave: Mediating effect of moral distress - Kovanci, Mustafa Sabri (Nursing ethics, 2025)
AimsThis study aims to examine the mediating effect of moral distress on the relationship between moral resilience and the intention to leave.BackgroundMoral distress is a phenomenon that negatively impacts healthcare workers, healthcare institutions, and recipients. To eliminate or minimize the negative effects of moral distress, it is necessary to increase the moral resilience of nurses. Moral resilience is important in protecting against the negative effects of moral distress, such as burnout and turnover intention. In this direction, it is necessary to increase the moral resilience of nurses to reduce negative situations such as turnover intention in nurses.MethodsIt is a descriptive–predictive study. Sociodemographic Information Form, Measure of Moral Distress – Healthcare Professionals, and Rushton Moral Resilience Scale were used to collect data from the nurses. A total of 220 clinical nurses were recruited.Ethical considerationsApproval was obtained from the university’s non-interventional ethics committee, and informed consent was obtained from the participants.ResultsThe study found a total moral distress score of 6.39 ± 0.3.12 and moral resilience score of 2.69 ± 0.48. A moderate and weak negative correlation was found between moral distress and moral resilience. Moral distress has a moderating effect on the intention to leave nursing (β = −0.158, p = .010) and the intention to leave the current position (β = −0.174, p = .000). Individual’s moral resilience directly affects the intention to leave. The presence of moral distress eliminates the direct effect of moral resilience and affects the intention to leave together with moral resilience.ConclusionsMoral resilience leads to decreased intention to leave, and moral distress mediates this situation. An increase in moral distress decreases moral resilience and increases intention to leave. It can be assumed that if moral distress is not controlled, increasing moral resilience will not affect the intention to leave the job.